STRATEGIES OF THE INDUSTRIAL ENTERPRISES ECONOMIC DEVELOPMENT WITHIN CITIES INFRASTRUCTURE DEVELOPMENT: STRATEGIES OF THE INDUSTRIAL ENTERPRISES ECONOMIC DEVELOPMENT WITHIN CITIES INFRASTRUCTURE DEVELOPMENT - Serheevich, Teletov; Yevhenevna, Letunovskaia; Vasilevich , Provozin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article deals with author’s proposals concerning development of the partner relationships in the socially significant problems sphere, particularly in the regional infrastructure. The local community represented by citizens and authorities, enterprises and workers are considered to be interested parties by author. The article presents researches on strategic partnership peculiarities in social and economic sphere; systematizes methods to stimulate enterprises to realize infrastructure projects from state; suggests complex approach to develop industrial regions, based on clustering, using of tech parks etc.